Ecology of Piliostigma Thonningii in Early Successional Plot in Northwestern Nigeria - Mbaekwe, E. I.; Isichei, A. O. (2014)
In the Kainji Basin, Mokwa and Yelwa areas of northwestern Nigeria early successional plots are usually dominated in terms of number of stems by the Caesalpinioid shrub Piliostigma thonningii. An ecological study of 17 sample plots from the areas was carried out in order to define the niche of Piliostigma because of its potential in providing soil cover and rehabilitation of degraded lands. In the plots studied it was found that Piliostigma abundance was associated with a high soil sand: clay ratio, open vegetation canopy and low species diversity. These characteristics identify Piliostigma as an early successful species.